2019
DOI: 10.5194/angeo-37-429-2019
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of GNSS tropospheric gradients to processing options

Abstract: Abstract. An analysis of processing settings impacts on estimated tropospheric gradients is presented. The study is based on the benchmark data set collected within the COST GNSS4SWEC action with observations from 430 Global Navigation Satellite Systems (GNSS) reference stations in central Europe for May and June 2013. Tropospheric gradients were estimated in eight different variants of GNSS data processing using precise point positioning (PPP) with the G-Nut/Tefnut software. The impacts of the gradient mappin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 39 publications
5
31
0
Order By: Relevance
“…Kačmařík et al (2019) report gradient amplitudes of up to 3-4 mm during the passage of an occlusion front over Germany. Nahmani et al (2019) studied gradients during the passage of mesoscale convective systems in West Africa and Koulali et al (2012) showed correlations between gradients and precipitation and moisture fluxes in Morocco. Other specific weather phenomena that can cause horizontal variability in the partial pressure of water vapour, and hence also the wet refractivity, are sea breeze (Craig et al, 1945;Miller et al, 2003), cloud rolls (Brown, 1970), and convection processes in general.…”
Section: Cause Of Horizontal Gradients and Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kačmařík et al (2019) report gradient amplitudes of up to 3-4 mm during the passage of an occlusion front over Germany. Nahmani et al (2019) studied gradients during the passage of mesoscale convective systems in West Africa and Koulali et al (2012) showed correlations between gradients and precipitation and moisture fluxes in Morocco. Other specific weather phenomena that can cause horizontal variability in the partial pressure of water vapour, and hence also the wet refractivity, are sea breeze (Craig et al, 1945;Miller et al, 2003), cloud rolls (Brown, 1970), and convection processes in general.…”
Section: Cause Of Horizontal Gradients and Modelsmentioning
confidence: 99%
“…Of specific interest in our study was to investigate if there is any systematic seasonal behaviour in the estimated gradients in Sweden and if they can be explained by the influence of regional-scale weather systems. The question about the seasonal changes of gradients was previously studied by Koulali et al (2012). Another issue is that comparisons of estimated GPS gradients with a high temporal resolution are rather sparse and have, to our knowledge, so far not covered periods of many years.…”
Section: Introductionmentioning
confidence: 99%
“…During GNSS data processing, other parameters were also estimated and this might introduce some errors in the results. Gradients are also sensitive to the processing settings, such as the elevation cutoff angle, gradient mapping function, and GNSS constellation, as shown by Kačmařík et al (2019).…”
Section: Comparison With Gradients From Gradmentioning
confidence: 99%
“…Several mapping functions have already been published, for instance the Global Mapping Functions, GMF (Böhm et al, 2006a), and the Vienna Mapping Functions 1, VMF1 (Böhm et al, 2006b). Recently, a refined version of VMF1, VMF3 (Landskron and Böhm, 2017), was released.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancies found between the different sources can be explained by the fact that the external source applies flat weighting on the observations, while TOMION makes use of negative exponential of the elevation angle of the transmitter. Another cause of scale differences can be the different mapping functions used for the gradient term: Chen and Herring () in TOMION and Bar‐Sever et al () in GIPSY, and as it is stated in Kačmařík et al (), systematic errors effects of up to 0.3 mm were observed in estimated tropospheric gradients when using different gradient mapping functions which depend on the applied observation elevation‐dependent weighting as well. Furthermore, in TOMION, we use VMF1, whereas UNR adopts GMF (Global Mapping Function; Böhm et al, ) for mapping the symmetric term ( m d and m w in equation ).…”
Section: Gps Processing and Validationmentioning
confidence: 99%